Managing the Global Economy - Michie Jonathan; Smith Grieve John (Oxford University Press, 1997)
This book examines current issues in the world economic order, and asks what new initiatives are necessary to ensure stability, growth and high levels of employment. Foreword, Introduction, Lessons from History, Trade and Growth: A Historical Perspective, The Bretton Woods System: Concept and Practice, Taming International Finance, Labor and Capital, Employment and Unemployment - North and South, Globalization and Labor Standards, Transnational Corporations and the Nation State, International Capital Movements: Some Proposals for Reform, International Finance and Exchange Rate Policy, International Finance Markets and National Transmission Mechanisms, Derivatives: A Growing Threat to the International Financial System, Managing the Exchange Rate System, Lessons of Exchange Rate Targeting, The Role of Government: National and International, The International Origins of Unemployment, A Program for Reform, A Postscript, Bibliography, Name and Subject Index.